Refleksi Siyasah Syar’iyah Terhadap Krisis Legitimasi Elite Moderen - Ghafur, Muh. Abdul; Asyiari, Muh. Wafdan; Kurniati, Kurniati (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The legitimacy crisis of modern elites is an increasingly evident issue in contemporary constitutional practice, where power obtained legally through democratic procedures is not always followed by substantive public acceptance and trust. This research aims to analyse the root causes of the modern elite legitimacy crisis and to reflect on it through the perspective of siyasah syar'iyyah as an ethical-normative framework within fiqh siyasah. This study employs normative legal research of the library research type, using a statutory-conceptual and comparative-conceptual approach, analysed descriptively and qualitatively through content analysis. The findings indicate that the modern elite legitimacy crisis fundamentally stems from a gap between procedural and substantive legitimacy, marked by weak accountability, expanding oligarchy, and democratic formalism without substance. The siyasah syar'iyyah perspective offers five evaluative principles: amanah and al-mas'uliyyah al-ijtima'iyyah, syura as the basis of participatory legitimacy, al-'adalah as a measure of substantive legitimacy, the maxim tasharruf al-imam 'ala al-ra'iyyah manutun bi al-maslahah, and hisbah as a mechanism of social control. This research concludes that strengthening these substantive values within state practice may serve as a solution for restoring the ethical and social legitimacy of modern elites, without necessarily rejecting the framework of modern democracy itself.